Egr1 plays a major role in the transcriptional response of white adipocytes to insulin and environmental cues - Meriin, A. B.; Zaarur, N.; Roy, D.; Kandror, K. V. (Frontiers in Cell and Developmental Biology, 2022)
It is believed that insulin regulates metabolic functions of white adipose tissue primarily at the post-translational level via the PI3K-Akt-mediated pathway. Still, changes in transcription also play an important role in the response of white adipocytes to insulin and environmental signals. One transcription factor that is dramatically and rapidly induced in adipocytes by insulin and nutrients is called Early Growth Response 1, or Egr1. Among other functions, it directly binds to promoters of leptin and ATGL stimulating the former and inhibiting the latter. Furthermore, expression of Egr1 in adipocytes demonstrates cell autonomous circadian pattern suggesting that Egr1 not only mediates the effect of insulin and nutrients on lipolysis and leptin production but also, coordinates insulin action with endogenous circadian rhythms of adipose tissue.